2021
DOI: 10.3389/fcimb.2021.652617
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio Bacteria Are Associated With Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the most prevalent movement disorder known and predominantly affects the elderly. It is a progressive neurodegenerative disease wherein α-synuclein, a neuronal protein, aggregates to form toxic structures in nerve cells. The cause of Parkinson’s disease (PD) remains unknown. Intestinal dysfunction and changes in the gut microbiota, common symptoms of PD, are evidently linked to the pathogenesis of PD. Although a multitude of studies have investigated microbial etiologies of PD, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 78 publications
(104 reference statements)
8
99
0
2
Order By: Relevance
“…Desulfovibrio also correlated with worse motor function, consistent with a previous study showing correlation with worse Hoehn and Yahr score [33]. Species of Desulfovibrio are dominant among intestinal sulfate-reducing bacteria, with a capacity for producing hydrogen sulfide, which is potentially toxic in humans [33].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Desulfovibrio also correlated with worse motor function, consistent with a previous study showing correlation with worse Hoehn and Yahr score [33]. Species of Desulfovibrio are dominant among intestinal sulfate-reducing bacteria, with a capacity for producing hydrogen sulfide, which is potentially toxic in humans [33].…”
Section: Discussionsupporting
confidence: 88%
“…Desulfovibrio also correlated with worse motor function, consistent with a previous study showing correlation with worse Hoehn and Yahr score [33]. Species of Desulfovibrio are dominant among intestinal sulfate-reducing bacteria, with a capacity for producing hydrogen sulfide, which is potentially toxic in humans [33]. Higher sulfate-reducing bacterial activities and consequent higher hydrogen sulfide production are believed to play a role in the development of inflammatory bowel disease [34], which has parallels with changes in the PD gut [27].…”
Section: Discussionsupporting
confidence: 86%
“…In case the iron content of the LIP reaches abnormally high levels, ROS formation in the cell eventually increases [26,28]. The possible presence of magnetite nanoparticles produced by some Desulfovibrio gut bacteria may be an additional factor in the increase in cytosolic ROS levels in the gut cells [13,29,30]. The increased ROS formation likely favors the emergence of aSyn oligomers and fibrils in the presence of Cyt c and aSyn (Figure 1) producing gut bacteria raises H2S concentrations in the gut cells and blood.…”
Section: H 2 S Releases Cytochrome C From the Mitochondria-start For ...mentioning
confidence: 99%
“…High H 2 S concentrations are toxic to cells, causing the inhibition of the cytochrome oxidase, a hemeprotein which is the last enzyme of the electron transport chain in the mitochondria [11]. In addition, H 2 S induces a release of cytochrome c protein from the mitochondrial membrane, an event though to be associated with the etiopathogenesis of Parkinson's disease (PD) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A simulation of the gut H 2 production based on the previously reported microbiota composition found a more than 2-fold reduction in the amount of produced H 2 in patients with PD compared with controls [ 80 ]. Interestingly, a recent study on 20 patients with PD and 20 healthy controls found that the gut microbiota of PD had significantly higher levels of Desulfovibrio , a hydrogen sulfide producing hydrogenotrophic bacteria, the authors speculating that the LPS, hydrogen sulfide and magnetite produced by the strains of the Desulfovibrio bacteria could trigger alpha-synuclein conformational changes and aggregation [ 82 ]. Concurrently, hydrogen sulfide was shown to have both beneficial (i.e., neuroprotection, increase in neurogenesis) and deleterious effects in animal models of PD [ 82 , 83 ].…”
Section: Molecular Hydrogen and Pdmentioning
confidence: 99%